Strategi Pengembangan Produk Pupuk Organik melalui Pendekatan New Product Development: Studi Kasus “Pupukin!” - Dira Purwasih; Prili Alisha; Rizqia Nadira Ronaldo; Stanislaus Adhi Pramudya; Muhammad Yasyfa Kusumadinata; Eddy Renaldi; Vira Kusuma Dewi (Universitas Galuh, 2026)
Pupukin! is an innovative slow-release organic fertilizer product with multifunctional 3-in-1 benefits (biofertilizer, biopesticide, biostimulant). This product was developed in response to challenges faced by urban farming practitioners, namely time constraints (time poverty) and reliance on inorganic fertilizers. While innovative products such as Pupukin! offer practical solutions, an appropriate development strategy is required to achieve commercial success. This study aims to analyze the product development strategy of Pupukin! using the New Product Development (NPD) approach and evaluate the effectiveness of the implemented NPD process based on consumer responses. The research employs a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews with the development team and consumers, observations, and document analysis. The results indicate that the implementation of NPD in Pupukin! followed systematic stages from idea generation to market testing. Strategic evaluation revealed successful product differentiation based on market needs. However, weaknesses were identified in concept validation and packaging design, which hindered effective communication of the product's value. The implications of this study emphasize the importance of integrating ongoing consumer validation at every stage of NPD to enhance the competitiveness of innovative organic fertilizer products.